Interface transmissivity of conventional and multicomponent GCLs for three permeants. Issue 1 (February 2019) - AbdelRazek, A.Y.; Rowe, R. Kerry
Abstract: A laboratory investigation of the interface transmissivity is reported for five different geosynthetic clay liners (GCLs) and a range of different geomembranes (GMBs) for a range of stresses from 10 to 150 kPa. The GCLs were prehydrated under normal stress before permeation. The GCLs examined comprised three multicomponent (a smooth coated, a smooth laminated, and textured coated) and two conventional (one with granular and one with powdered sodium bentonite) GCLs. The effect of a 4 mm circular defect in the coating of a multicomponent GCL directly below the 10 mm diameter hole in the GMB is investigated. The effect of GMB stiffness and texture is examined. Additionally, the effect of hydration and permeation of smooth coated GCL with highly saline solution and synthetic landfill leachate (SL3) is presented. It is shown that the 2-week interface transmissivity ( θ 2-week ) can be one to two orders of magnitude higher than steady-state interface transmissivity ( θ steady-state ) at low stresses (10 kPa–50 kPa), whereas at high stresses (150 kPa) the variation is substantially less. For a smooth coated GCL hydrated and permeated with reverse osmosis (RO) water, GMB stiffness and texture has a limited effect on interface transmissivity when the coating is placed in contact with GMB at normal stresses of 10 kPa–150 kPa, whereas coating indentations result in much high interface transmissivity when placed in contact with GMB. GCL prehydration and permeation with highly saline solutions leads to higher interface transmissivity compared to RO water. With a 4.0 mm defect in the coating, the interface transmissivity between the coating and woven geotextile is higher than that between the coating and GMB for the stress levels and GCL examined.